DRAINAGE GEOCHEMISTRY AROUND THE ABANDONED WHITTLE COLLIERY, NORTHUMBERLAND, UK - Kalender, Leyla (Springer Heidelberg, 2010)
An investigation was conducted on the drainage geochemistry and mineralogy of stream sediments in the area of the Fe-Mn passive treatment system in Whittle Colliery, UK. The major and trace element concentrations were analyzed in the surface waters as well as in the different fractions (<75; <106; <150; <180 mu m) of the riverbed sediments and plants (algae and moss). The system comprises a series of 2 lagoons and 3 reed bed wetlands that contaminate the groundwater that is pumped to the surface in order to prevent uncontrolled surface mine water discharge that would occur after mine water rebound without the proper management intervention. It was observed that the passive treatment system is most effective at decreasing Fe, Al, and Mn concentrations in groundwater, although a significant contamination of surface waters is still observed in places. The results of the present study show that the adsorption processes and mixing between the tributaries and seepage of mine waters (wetland II) alter the mineralogical composition of the riverbed sediments and surface water compositions around the passive treatment system. Therefore, given the higher concentrations of the biota downstream of the treatment discharge relative to the control locations show some plants' uptake/biosorption. High bicarbonate and carbonate contents, high buffering capacity, and the greater protection of aquatic life in the receiving stream, the SO4 concentrations were found to be above the EQS values (Environmental Quality Standards) at most of the sample locations. Calcium ions were lost by ion exchange to create calcium sulfate water as carbonate facies water interacted with pyrite. For that reason, special caution has to be taken in order to remove these contaminant anions.
Keywords: heavy metal; ICP; EDS; SEM; XRD; abandoned Whittle Colliery; passive treatment